Pengambilan Keputusan Tugas Belajar ASN di BKD Provinsi Sumatra Barat - Isabel Putriyadi; Jefri Ardivo; Laura Mah Aulia; Naaifa Rasi Mutliq; Putri Ramadhani; Syafni Shabrina; Syamsir . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
The implementation of study assignments for State Civil Apparatus (ASN) at the Regional Personnel Agency of West Sumatra Province still faces various administrative obstacles and regulatory dynamics that influence the decision-making process. Frequently occurring problems include incomplete documents, administrative delays, and policy changes that require rapid procedural adjustments. These conditions cause the process of determining study assignments to require more complex coordination and organizational considerations. Furthermore, ASN are still found to begin education before the study assignment decision letter is issued, thus affecting the effectiveness of the administrative and verification processes within the BKD. This study aims to analyze the decision-making process for ASN study assignments at the BKD of West Sumatra Province, identify the administrative obstacles faced, and explain the organization's strategies in supporting ASN competency development. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Research informants were selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data presentation, and conclusion drawing. The results show that the study assignment decision-making process is carried out through systematic administrative stages based on regulations and organizational needs. The Regional Civil Service Agency (BKD) plays a crucial role in administrative verification, inter-agency coordination, and ASN competency development through the Human Capital Development Plan (HCDP) and administrative digitization using the SRIKANDI application. Research findings also indicate that an organization's ability to adapt to regulatory changes is a crucial factor in maintaining effective administrative services and ASN competency development within local governments